Pemberdayaan Kelompok Perempuan Penenun dalam Pengembangan Ekonomi Lokal dan Pelestarian Budaya - Riwu, Yonas Ferdinand; Bunga, Markus; Aman, Dominikus K. T; Sinlae, Yoan Tania; Djo, Rini Aryani (Abdimas Mandalika, 2025)
Abstract:  Sabu weaving has its own attraction and has become an economic source for the Sabu community, especially women weavers. This service aims to empower women weavers so that they are able to adapt to the changing times, increase income and understanding in digital-based marketing, and maintain the preservation of Sabu weaving culture. The direct education and public assistance method involves involving the "Winirai" Weaver Women's Group which totals 16 people. The result of this service activity is the improvement of skills, the use of technology and marketing strategies through social media with the storytelling method with the strengthening of the narrative about the culture of Sabu Raijua weaving. In addition, this PKM realizes the preservation of the culture and heritage of Sabu weaving in increasing awareness of cultural values and weaving traditions among the younger generation.Abstrak: Tenun Sabu memiliki daya tarik tersendiri dan telah menjadi sumber ekonomi masyarakat Sabu terutama perempuan penenun. Pengabdian ini bertujuan unuk pemberdayaan perempuan penenun sehingga mampu beradaptasi dengan perubahan jaman, meningkatkan pendapatan dan pemahaman dalam pemasaran berbasis digital, dan mempertahankan pelestarian budaya tenun Sabu. Metode edukasi langsung dan public assistance dengan melibatkan melibatkan Kelompok Perempuan Penenun “Winirai” yang berjumlah 16 orang. Hasil dari kegiatan pengabdian ini yaitu adanya peningkatan keterampilan, pemanfaatan teknologi dan strategi pemasaran melalui media social dengan metode storytelling dengan penguatan narasi menganai budaya dari tenunan Sabu Raijua. Selain itu PKM ini, mewujudkan pelestarian budaya dan warisan tenun Sabu dalam meningkatkan kesadaran akan nilai-nilai budaya dan tradisi tenun di kalangan generasi muda.